2000
DOI: 10.1093/jat/24.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Tetrachloroethylene and Trichloroethylene Fatality: Case Report and Simple Headspace SPME-Capillary Gas Chromatographic Determination in Tissues

Abstract: We describe a simple, precise, and sensitive assay of tetrachloroethylene and trichloroethylene in tissues, suitable both for emergency cases and forensic medicine. The method employs headspace solid phase microextraction-capillary gas chromatography and electron capture detection. The case is relative to a 45-year-old woman discovered unconscious in a laundry area. The concentrations of the solvents in tissues were determined and compared to other previously published fatalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 28 publications
0
25
0
2
Order By: Relevance
“…É uma matriz com moderada complexidade e tipicamente contém compostos inorgânicos e orgânicos, com quantidade relativamente grande de sais. 59,60 A eficiência na extração pode variar devido a diversas razões. Variações no pH da urina afetam a eliminação de muitos fármacos, assim como variações na força iônica alteram a viscosidade da amostra, promovendo efeitos significantes na extração.…”
Section: Urinaunclassified
“…É uma matriz com moderada complexidade e tipicamente contém compostos inorgânicos e orgânicos, com quantidade relativamente grande de sais. 59,60 A eficiência na extração pode variar devido a diversas razões. Variações no pH da urina afetam a eliminação de muitos fármacos, assim como variações na força iônica alteram a viscosidade da amostra, promovendo efeitos significantes na extração.…”
Section: Urinaunclassified
“…Timecourse studies in rats dosed with TCE indicated that, over a 24 h period, the amount of metabolites (particularly TCA) increased, peaking at 8 h post-dosing. Dehon et al (2000) report a method for analyzing TCE, TCA, TCEOH and PCE in a human fatality case. Levels of PCE, TCEOH and TCA were measured from days 0-7 of hospitialization (the patient died on day 7) and generally decreased over time.…”
Section: Gas Chromatographymentioning
confidence: 99%
“…It is also interesting to note that Xie (2001) was able to obtain cleaner chromatograms with fewer interfering peaks and lower MDLs for HAAs using EPA Method 552.2 with a single quadrupole mass spectrometer instead of an ECD. Single quadrupole mass spectrometers are predominantly used with GC methods and have been utilized for the GC-MS analysis of TCE in urine (Song and Ho, 2003) and tissues (Dehon et al, 2000), DCA in plasma and CH in plasma (Yan et al, 1999;Henderson et al, 1997). In addition, HPLC (Takino et al, 2000;Hashimoto and Otsuki, 1998;Loos and Barcelo, 2001) and CE methods (Ahrer and Buchberger, 1999) coupled with single quadrupole mass spectrometers also exist for the analysis of HAAs in water samples.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Un cas d'intoxication mortelle suite à une exposition accidentelle au tétrachloroéthylène d'une femme a été décrit par Dehon et al (14). Le tétrachloroéthylène, le trichloroéthylène et leurs metabolites ont pu être quantifié dans le sang, les urines et les tissus de la victime après extraction par les fibres SPME et analyse par CPG/SM.…”
Section: La Microextraction Par Fibreunclassified